Singapore’s ‘Crazy Rich Asians’ experience of city branding - TAN, Chee Wei (Institutional Knowledge at Singapore Management University, 2019)
Tourism has been an important economic pillar for Singapore for decades, contributing 4% to Singapore’s Gross Domestic Product (GDP). While Singapore is a well-known destination with Asians and Europeans, the country has yet to become a popular choice for US travellers who lived outside the gateway cities on the eastern and western coasts. Being the second largest economy in the world, the US presents huge potential for tourism in Asia, and specifically Singapore. Under the premise of the ‘Passion Made Possible’ brand for Singapore, jointly launched by the Singapore Tourism Board (STB) and the Singapore Economic Development Board (EDB) in 2017, STB collaborated with Warner Bros. in promoting the film Crazy Rich Asians, a Hollywood romantic comedy based on a book by the same title. The film’s huge success has helped raise the profile of Singapore in the US market. However, there were some misalignments in the interplay of STB’s city branding vision, the cultural connection to Singaporeans and the image that US travellers had of Singapore.